2013
DOI: 10.1186/1471-2105-14-s6-s7
|View full text |Cite
|
Sign up to set email alerts
|

On the computational modeling of the innate immune system

Abstract: In recent years, there has been an increasing interest in the mathematical and computational modeling of the human immune system (HIS). Computational models of HIS dynamics may contribute to a better understanding of the relationship between complex phenomena and immune response; in addition, computational models will support the development of new drugs and therapies for different diseases. However, modeling the HIS is an extremely difficult task that demands a huge amount of work to be performed by multidisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Almost all parameters used in the simulation were obtained in Marchuk [44] applying the necessary unit conversions and some fitting to the coupled model. The only exceptions are the diffusion coefficients D M R , D M A , and D F which were estimated by Pigozzo et al [42] and the diffusion coefficient of bacteria D A based on the work of Haessler and Brown [62]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all parameters used in the simulation were obtained in Marchuk [44] applying the necessary unit conversions and some fitting to the coupled model. The only exceptions are the diffusion coefficients D M R , D M A , and D F which were estimated by Pigozzo et al [42] and the diffusion coefficient of bacteria D A based on the work of Haessler and Brown [62]. …”
Section: Methodsmentioning
confidence: 99%
“…The model has been extended (a) to allow the use of a three-dimensional domain in order to better represent the site of infection and (b) to use parallel programming techniques to guarantee a reasonable simulation time [43]. This work extends our previous models [42, 43], enabling the innate IS to activate the adaptive one. The main contribution of this work is a mathematical model that reproduces the dynamics of both innate and adaptive IS, coupling for this purpose models of different nature and scales.…”
Section: Introductionmentioning
confidence: 99%
“…Computational studies of inflammation can be divided between acute and chronic inflammation, which both focus on, but consider different aspects of, the innate immune system [134][135][136][137][138][139][140][141]. Inflammation is a response by the immune system to injury or infection and involves three basic steps: (1) sensing of damage or threat; (2) containment and clearance of the threat; and (3) repair of the damaged tissue.…”
Section: Computational Modeling Of Host Immune Systemmentioning
confidence: 99%
“…Although from the perspective of understanding the immune response, innate immunity has already been proposed a while ago to be most suitable for systems biology studies (10), the number of mathematical models focusing on this innate immunity is still limited (22), yet the innate immune system plays an important role in effective host defense against bacterial and viral infections (23,24) and possibly in allergies and tumorigenesis, and there may already be sufficient information to construct explicit mechanism-based systems biology models. A comprehensive map of IgE-mediated mast cell activation (25) might be used to explore both the intracellular and population dynamical properties of the corresponding section of the immune system, and the experimental field is now reporting genomewide experimental data sets, which systems biology can integrate and help understand in terms of the emergence of function (10).…”
Section: Introductionmentioning
confidence: 99%
“…Mavroudis et al (30) showed how stochasticity can be taken into account, which they did essentially for the simpler four-variable model referred to above. Other authors extended these models to include spatial dimensions and multiscale aspects (22,31), the latter authors shifting to a Boolean approach.…”
Section: Introductionmentioning
confidence: 99%